2010
DOI: 10.1142/s0217751x1004930x
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative Thermofield Dynamics

Abstract: The real-time operator formalism for thermal quantum field theories, thermofield dynamics, is formulated in terms of a path-integral approach in non-commutative spaces. As an application, the two-point function for a thermal non-commutative λφ 4 theory is derived at the one-loop level. The effect of temperature and the non-commutative parameter, competing with one another, is analyzed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
0
12
0
2
Order By: Relevance
“…whereḠ is an unitary operator mixing |n ∈ H and |ñ ∈H by acting on the Hilbert space H ⊗H, similarlly to (16) and (17), but with a two-mode squeezing operator form 35 ,Ḡ…”
Section: No-cloning Theorem In Thermofield Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…whereḠ is an unitary operator mixing |n ∈ H and |ñ ∈H by acting on the Hilbert space H ⊗H, similarlly to (16) and (17), but with a two-mode squeezing operator form 35 ,Ḡ…”
Section: No-cloning Theorem In Thermofield Dynamicsmentioning
confidence: 99%
“…TFD approach has been largely applied in the study of finite temperature systems, from high energy physics 13,14,15,16,17 to quantum optics 18,19,20,21,22,23 and condensed matter physics 24,25,26 , in different contexts as gauge theories 27 , Anderson model 26 , renormalization group 28 , Casimir effect 29,30 , string field theory 31 , supersimmetry 32 , noncommutative theories 15,16 , non-classical states 21 , thermal and quantum fluctuations 33 , master equations 11 , among others 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The algebraic structure of non-commutative geometries has been developed along different lines, in particular in association with c*-algebras [7]. The interest in noncommutative theories, since the 1990s, is due to a variety of applications [1,8], including abelian and non-abelian gauge theories [8][9][10][11], gravity [12,13], standard model for particles [15,16], supersymmetry [17] and in quantum Hall effect [18]. Issues such as the ultraviolet/infrared mixing and the renormalizability of noncommutative theories have been also addressed [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Gauge field theories with nonabelian gauge groups are constructed in [16,17]. Construction of thermal field theories is done in [18][19][20] while [21] discusses the twisted bosonization in two dimensional noncommutative spacetime. A comprehensive review of twisted field theories can be found in [3].…”
Section: Introductionmentioning
confidence: 99%